2015
DOI: 10.1051/epjn/e2015-50027-y
|View full text |Cite
|
Sign up to set email alerts
|

Why nuclear energy is essential to reduce anthropogenic greenhouse gas emission rates

Abstract: Abstract. Reduction of anthropogenic greenhouse gas emissions is advocated by the Intergovernmental Panel on Climate Change. To achieve this target, countries have opted for renewable energy sources, primarily wind and solar. These renewables will be unable to supply the needed large quantities of energy to run industrial societies sustainably, economically and reliably because they are inherently intermittent, depending on flexible backup power or on energy storage for delivery of base-load quantities of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Ironically, empirical studies found that a policy attempt at expanding renewables might not even reduce coal-based electricity and embedded greenhouse-gas emissions (e.g., [57]). Ultimately, as the urgency of climate change mitigation mounts and as requirements for sustainable growth in developing economies and the replacement of aging infrastructure in the developed world come to the fore, pragmatic decisions on the economic and logistical viability of all types of non-fossil technologies will have to be made rationally and with consideration to their respective benefits and limitations [58].…”
Section: Alternative Energy Mixes and The "Silver Buckshot"mentioning
confidence: 99%
See 2 more Smart Citations
“…Ironically, empirical studies found that a policy attempt at expanding renewables might not even reduce coal-based electricity and embedded greenhouse-gas emissions (e.g., [57]). Ultimately, as the urgency of climate change mitigation mounts and as requirements for sustainable growth in developing economies and the replacement of aging infrastructure in the developed world come to the fore, pragmatic decisions on the economic and logistical viability of all types of non-fossil technologies will have to be made rationally and with consideration to their respective benefits and limitations [58].…”
Section: Alternative Energy Mixes and The "Silver Buckshot"mentioning
confidence: 99%
“…It has all of the crucial attributions required of a clean-energy "techno-fix", in that: (i) it offers the feasible prospect of a "plug in" replacement for coal-and gas-fired electricity; (ii) its process heat or excess electrical output can be used for synfuel manufacture and other industrial applications to replace oil; and (iii) this next generation of nuclear power systems avoids many of the real and perceived problems of current-generation reactor technology [31,[58][59][60][61].…”
Section: Integral Fast Reactors-an Exemplar "Silver Bullet" Clean-enementioning
confidence: 99%
See 1 more Smart Citation
“…When the sun doesn't shine and the wind won't blow, we all know we need reliable on-demand electric power at a reasonable cost. As Alonso, et al [5] point out, averaged over a year, wind/solar systems deliver 25% to 45% of their nameplate production capacity. Thus backup power plants (with rapid startups) or adequate energy storage facilities (which do not currently exist) would have to deliver the remaining 55% to 75% of electricity, based on the renewable nameplate deficit.…”
Section: Renewablesmentioning
confidence: 99%